Chapter Evaluation and monitoring of the Livorno's Fossi System - Montioni, Laura (Proceedings e report, 2020)
The ditches and canals of Livorno, also called Fossi, are the most characterized elements the city, not only from a historical point of view, but also and above all from an urban landscape characterization point of view. Due to the overlapping of skills not yet resolved, fragmented information and data exist regarding the real extent of the pleasure craft, the status of the canals, the provision of services and general safety. The hypothesis is to succeed, through a multi-criteria assessment of scenarios, to support and quantify the displacement of vessels that negatively affect accessibility and the landscape of Livorno's Fossi system elsewhere.